Federalism : origin and application - Saleem, Muhammad Yusuf (Cengage Learning, 2008)
Federalism has been a central aspect of Malaysian history since the establishment of the Federated Malay States in 1895. Ever since the idea of federalism was mooted by the British, it has been a subject of intense discussion. The idea went through various stages of centralisation and decentralisation. Finally Malaya emerged as an independent state in 1957 with a Federal Constitution. This chapter discusses the various centripetal and centrifugal trends that influenced the federal idea between 1895 and 1957. This is followed by an analysis of the distribution of legislative powers between federal and state governments including the power of the parliament to legislate on certain state subjects. The last section of the chapter discusses the federal features of the 1957 Constitution and shows how these features benefitted from the process of evolution that the idea of federalism has undergone since 1895.